2017
DOI: 10.1038/s41598-017-03229-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of Polymorphisms in Pharmacogenetic Candidate Genes with Propofol Susceptibility

Abstract: Significant individual susceptibility to intravenous anesthetic propofol exists. The etiology of individual variability in the response to propofol may be influenced by genetic polymorphisms in metabolic and functional pathways. With current pharmacogenetics and modern molecular biology technologies, it is possible to study the influence of genetic polymorphisms on susceptibility to propofol. When inducing general anesthesia with intravenous propofol, high individual susceptibility to propofol was found. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 62 publications
1
34
1
1
Order By: Relevance
“…Changing rs6746030 in SCN9A from G to A can change the function of the sodium channel; changes in glutamate release and intrinsic ionic conductivity resulted in greater susceptibility to propofol, which is shown by significantly lower BIS values after propofol-induced unconsciousness. This result may help clarify the role of SCN9A in propofol sensitivity [23].…”
Section: P H a R M A C O G E N E T I C S : R E L E V A N C E F O R T mentioning
confidence: 74%
See 3 more Smart Citations
“…Changing rs6746030 in SCN9A from G to A can change the function of the sodium channel; changes in glutamate release and intrinsic ionic conductivity resulted in greater susceptibility to propofol, which is shown by significantly lower BIS values after propofol-induced unconsciousness. This result may help clarify the role of SCN9A in propofol sensitivity [23].…”
Section: P H a R M A C O G E N E T I C S : R E L E V A N C E F O R T mentioning
confidence: 74%
“…Variation of the C-To-a rs2283265 polymorphism in HRM2 resulted in lower heart rate values. Changes from G to a rs2279020 in GABAA1 are accompanied by a lower BP curve after propofol anesthesia [23].…”
Section: P H a R M A C O G E N E T I C S : R E L E V A N C E F O R T mentioning
confidence: 98%
See 2 more Smart Citations
“…Propofol, as one of the commonly used intravenous anesthetic agents, has variable pharmacokinetics attributed to genetic variation of the drug metabolizing enzymes. It undergoes metabolism by hepatic CYP2B6 enzyme and O -glucuronidation by UGT1A9.66 Polymorphisms of the genes coding for these enzymes affect elimination and clearance of propofol from the system resulting in discrepancies in the serum drug levels.67 For instance, patients with CYP2B6*4 alleles have been shown to have reduced drug clearance which increases their susceptibility to drug toxicity even with the regular doses.68 In another study, CYP2B6*6 has been demonstrated to be responsible for the differences in plasma drug levels and dose requirements.69 Additionally, propofol pharmacodynamics are affected by variations in the genes coding for GABA A target receptors (GABRE).70 Furthermore, another study suggests that the extensive variability of patient susceptibility could be attributed to a much greater range of genes including the dominant variations in GABAA1 rs2279020, GABAA2 rs11503014, and CHRM2 rs1824024.71 Cytochrome P450 family (CYP450), ATP-binding cassette (ABCB1), serine/threonine-protein kinase 3 (TAOK3), family with sequence similarity 53 member B (FAM53B), and the cannabinoid receptor (CNR1) are postulated to be involved in propofol pharmacokinetics; opioid receptors (OPRM1 and OPRD1), β-adrenoceptor (ADRB1), Catechol-O-methyltransferase (COMT), and ligand-gated ion channel (P2RX7) are postulated to be directly or indirectly involved in the pharmacodynamic response to propofol; nitric oxide synthase (NOS3), GABA type A (GABAA) receptor, NMDA receptors (GR1N3A and GR1N2B), Galanin (GAL), fatty acid amide hydrolase (FAAH), 5-hydroxytryptamine receptor (5HT2A), cholinergic receptors (CHRM2 and CHRNA5), dopamine transporters (DAT and DRD2), casein kinase (CSNK1E), calcium channels, potassium channels (KCNS1 and GIRK), and sodium channels (SCN9A) are also likely involved in the action of propofol. However, the gene variants so far studied have not shown any significant clinical differences.70…”
Section: Anestheticsmentioning
confidence: 99%